Fish gelatin from tilapia skin. - Bakar, Jamilah; G. K., Harvinder (2001)
Gelatin has a very broad application for e.g. in the food. pharmaceuticals, and photographic industries. Present commercial gelatins are produced from skins and bones of cows and pigs. However, in the last few years, gelatin from the skin of temperate fiSh has been produced in the United States. Fish skin is normally discarded in the filleting operation. Some recovery of the skin is possible in the deboning operation. Since, fish skins are potential source of gelatin, therefore a study on the extraction of gelatin for food application and the determination of the physicochemical characteristics of the gelatin obtained from black (Oreochromis mossambicus) and red (O.nilotica) tilapia skin was undertaken. Possible abundance of the talapia skin is seen as the outcome of the increase and the relative ease of tilapia culture in the country. Several extraction procedures are currently under study, however, the one involving washings with 0.2% (w/v) NaOH and sulfuric acid, and 1.0% (wlv) of citric acid is reported here. Visual appearance, odour, bloom strength, viscosity, melting point and the amino acid profile of the gelatins were evaluated. Both the gelatins of the black and the red tilapia were yellowish and light textured. Gelatins of black and red tilapias had strong fishy odour. Higher bloom strength was obtained from gelatin of black when compored to gelatin from red tilapia skin. Other studied properties of the gelatin obtained indicated that the gelatin from these two closely related fish species does not exhibit the same physico-chemical characteristics. This study also indicates that tilapia skin is a valuable source of 'halal' or koshered gelatin with functional properties suitable for the application in the food industries.